Double‐unit unrelated cord blood transplantation for thalassemia major: Comparison with HLA‐identical sibling bone marrow transplantation. (2nd November 2020) - Feng, Jianhua; Lee, Vincent; Leung, Alex W. K.; Lam, Grace K. S.; Chow, Terry T. W.; Cheng, Frankie W. T.; Yan, Carol L. S.; Lee, Cheuk Kwong; Yuen, Patrick M. P.; Li, Chi Kong
Abstract: UCBT recipients with TM are at high risk of EF related to low number of stem cells and prior alloimmunization after multiple blood transfusions. Here, we evaluated the safety and efficacy of double‐unit UCBT using TT‐containing conditioning regimens in TM. Retrospective analysis of children who underwent double‐unit UCBT for TM in the Prince of Wales Hospital between August 2007 and January 2017, and outcome of double‐unit UCBT for TM was compared with outcome of HLA‐matched sibling BMT. Ten patients, median age 4.2 years, received double‐unit UCBT. All patients except one engrafted at a median of 19 days. None of the patients with successful engraftment had grade III or IV aGVHD. Among nine patients with successful engraftment, six of nine patients evaluable after day 100 developed cGVHD. All patients with cGVHD were well controlled after treatment with steroids and/or supportive care and maintained good quality of life. In comparison with patients receiving BMT, those given UCBT had slower platelet recovery, and more cGVHD. With a median follow‐up of 272 months after BMT and 84 months after UCBT, the 8‐year OS after BMT and UCBT was 92% and 90% ( P = .84), whereas 8‐year DFS after BMT and UCBT was 87% and 80% ( P = .54). UCB could be an acceptable source of stem cells for transplantation of TM patients when HLA‐matched family bone marrow donors are NA.